Phylogenetic Analysis of Selected Chrysanthemum Species Using matK Gene Sequences: An In Silico Approach - Wilapangga, Anjas; Rakhmad Noordam, Errol; Yudianto, Dian (Journal Syifa Sciences and Clinical Research, 2025)
This study evaluated the effectiveness of the matK gene as a molecular marker for identifying and establishing phylogenetic relationships among species within the genus Chrysanthemum. DNA sequence data were retrieved from the NCBI database and analysed using MEGA X software with the UPGMA method and 1000 bootstrap replicates. The resulting phylogenetic tree showed clear species differentiation, with strong clustering between C. indicum and C. × morifolium, and distinct divergence among other species such as C. zawadskii, C. chanetii, and C. lucidum. These findings confirm that matK is a reliable DNA barcoding marker for systematic and taxonomic studies of Chrysanthemum, particularly in addressing the limitations of morphological identification caused by phenotypic variation and hybridisation. However, this study was limited to a single marker, and future research should incorporate additional loci or genomic approaches to obtain a more comprehensive understanding of Chrysanthemum phylogeny.